Pathological hip fractures. Issue 2 (April 2020) - Riemen, Anna HK; Aherne, Brigid; Bruce, Eilidh; Boddie, David E.; McCullough, Louise A.
Abstract: Pathological lesions and fractures in the proximal femur are a common presentation to orthopaedics. Key to getting the management right first time is careful assessment using a multidisciplinary approach. Early discussion with the local orthopaedic oncology service is paramount before any biopsy or surgical intervention is planned. This paper discusses several key pathologies that can result in lesions of the proximal femur and their optimal management.